Modalitas dalam sambutan Presiden Joko Widodo dalam peluncuran govtech Indonesia linguistik fungsional sistemik - Kurniawan, Bima; Puspitasari, Dyah; Firjatulloh, Nasywa Qatrunada; Tirtoaji, Wahyu; Viviana, Dwieke (CV. Kurnia Grup, 2024)
This research examines President Joko Widodo's speech at the launch of GovTech Indonesia using the theory of Systemic Functional Linguistics (SFL). This research aims to determine the use of modalities in the president's speech. The theory used in this research uses the theory of Halliday and Matthiessen (2004). The method used is a qualitative method with descriptive presentation. The findings in this research show that President Joko Widodo's welcoming text at the launch of GovTech Indonesia uses medium to high modalities, with the modalities of want, must, and also will. Overall, the choice of modality in President Joko Widodo's speech text reflects a measurable communication strategy which is the main key to making the message in the President's speech stronger and more influential. This aims to represent President Joko Widodo's ability to carry out his vision, plans and future improvements for the better welfare of the Indonesian state.